2004
DOI: 10.1097/01.pgp.0000139637.01977.61
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Neuroendocrine Carcinomas of the Uterine Cervix: A Histological, Immunohistochemical, and Molecular Genetic Study

Abstract: Small cell carcinomas of the uterine cervix are rare tumors with an aggressive behavior. Although these tumors can exhibit neuroendocrine differentiation, the criteria for neuroendocrine differentiation are subjective and not well defined. In this study, the authors tentatively defined small cell neuroendocrine carcinoma (SCNEC) as a tumor composed of small cells with at least two of the following: argyrophilic cytoplasm, chromogranin A immunoreactivity, and synaptophysin immunoreactivity. We found 10 cases fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 22 publications
5
48
0
Order By: Relevance
“…Generally speaking, SCCC is highly aggressive with regard to its biological behaviors. A previous study showed that the undifferentiated carcinoma of SCCC was closely related to HPV18 infection [11][12][13] . Herrington et al [14] believed that the absence of expression of pRb immunocompetence was likely to result from the combination of pRb with E7 protein of HPV virus, and, in SCCC, the lack of immunocompetence of pRb was related with the endocrine phenotype of small cells, which contributes to its aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, SCCC is highly aggressive with regard to its biological behaviors. A previous study showed that the undifferentiated carcinoma of SCCC was closely related to HPV18 infection [11][12][13] . Herrington et al [14] believed that the absence of expression of pRb immunocompetence was likely to result from the combination of pRb with E7 protein of HPV virus, and, in SCCC, the lack of immunocompetence of pRb was related with the endocrine phenotype of small cells, which contributes to its aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of a non-small cell component has recently been molecularly analyzed in SCCs of the cervix 7 and urinary bladder 9 and has led to the tentative conclusion that both components may have originated from undifferentiated multipotential or stem cells in the mucosa. Similarly, and despite the evidence of biphenotypical differentiation, the nearly identical pattern of allelic loss in our SCC and concomitant ADC support the hypothesis that they shared the same cellular origin.…”
Section: Discussionmentioning
confidence: 99%
“…Although originally believed to be an uncommon subtype of SCC, cervical SCC 6 is now recognized as a rare but distinct entity belonging to the neuroendocrine group of cervi- cal carcinomas, morphologically resembling SCC of the lung and clinically characterized by an aggressive course and unfavorable outcome. 7,8 Because some cervical SCCs (up to 70% according to some authors 7 ) may show a mixed or adjacent non-SCC component (ADC or squamous carcinoma) in the presence of SCC tumoral cells, it is important to seek malignant squamous or glandular cells. We failed to recognize the glandular component in our case on first screening and only found it on subsequent examination, when we were aware of the histologic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidences based on only a constrained number of NECA cases demonstrate that almost all of NECA cases are associated with HPV 16 and/or HPV 18. However, in contrast to that noted in SCCA, the most prevalent HPV type among NECA cases is HPV 18, followed by HPV 16 (Masumoto et al, 2003;Ishida et al, 2004;Wang et al, 2006). In a study from Northern Thailand which is the largest study conducted to determine HPV genotype distribution in NECA, almost 90% of cases of NECA are HPV 16 and/or HPV 18-related.…”
Section: Invasive Cervical Cancer (Icc)mentioning
confidence: 99%